Neuroscience of embodied reflection: somatic/mindbody/contemplative practices, health, and transformative learning. Issue 6 (1st November 2020) - Le Pertel, Noémie; Fisher, Jonathan; van Dam, Nick
ABSTRACT: Transformative learning harnesses reflection to create deep change in adult learners. These changes can be embodied in our neurobiological and cardiovascular systems. These physiological embodiments of transformative learning require health of body and mind. Contemplative practices including embodied reflective practices are technologies that can support the reintegration of body, brain, and mind, therefore supporting transformative learning and deep sustainable change.